Trends in undergraduate economics degrees, 1991–2014. Issue 1 (2nd January 2016) - Siegfried, John J.
Abstract: The 2007–10 growth spurt (18 percent over 3 years) in U.S. undergraduate economics degrees stalled in 2011. Degrees awarded were stagnant over the succeeding three years but show evidence of accelerating rapidly again in 2013–14.